INVESTIGATING EFL STUDENTS’ ONLINE ENGAGEMENT IN ZOOM MAIN ROOM AND BREAKOUT ROOMS - Natalie, Regina Yoantika; Purnamaningwulan, Rina Astuti (Sanata Dharma University Yogyakarta, 2024)
Zoom as one of the video conference applications facilitates synchronous online learning through its main room and breakout rooms features. This research aimed to compare students’ online engagement in Zoom main room and Breakout rooms. It also explored the extent to which group discussions could facilitate students' online engagement through Zoom Breakout rooms. Ninety-one EFL students participated in this mixed-method study. Quantitative data were collected using 24-item questionnaires addressed to two different groups of students: breakout room and main room students. Qualitative data were collected by interviewing six respondents from the breakout room group to explore their opinions regarding the breakout room’s effectiveness in promoting online engagement. The independent sample t-test towards the quantitative data revealed a significant difference between online engagement that occurred in the Breakout room compared to the Zoom main room (t=-4.922, df=89, p0.05). Further, it was found that Zoom breakout rooms were able to facilitate online engagement in the five engagement aspects, namely social, collaborative, behavioral, emotional, and cognitive engagement. These findings imply that Zoom Breakout rooms can be optimized to boost online engagement.